Electrochemical Reduction of Carbon Dioxide to Methanol on Hierarchical Pd/SnO2 Nanosheets with Abundant Pd–O–Sn Interfaces. Issue 30 (28th June 2018) - Zhang, Wuyong; Qin, Qing; Dai, Lei; Qin, Ruixuan; Zhao, Xiaojing; Chen, Xumao; Ou, Daohui; Chen, Jie; Chuong, Tracy T; Wu, Binghui; Zheng, Nanfeng
Abstract: Electrochemical conversion of CO2 into fuels using electricity generated from renewable sources helps to create an artificial carbon cycle. However, the low efficiency and poor stability hinder the practical use of most conventional electrocatalysts. In this work, a 2D hierarchical Pd/SnO2 structure, ultrathin Pd nanosheets partially capped by SnO2 nanoparticles, is designed to enable multi‐electron transfer for selective electroreduction of CO2 into CH3 OH. Such a structure design not only enhances the adsorption of CO2 on SnO2, but also weakens the binding strength of CO on Pd due to the as‐built Pd–O–Sn interfaces, which is demonstrated to be critical to improve the electrocatalytic selectivity and stability of Pd catalysts. This work provides a new strategy to improve electrochemical performance of metal‐based catalysts by creating metal oxide interfaces for selective electroreduction of CO2 . Abstract : Electrochemical conversion of CO2 : A two‐dimensional Pd/SnO2 structure, based on ultrathin Pd nanosheets partially capped by SnO2 nanoparticles, made possible multi‐electron transfer for the electroreduction of CO2 to CH3 OH. The upgraded adsorption of CO2 on the SnO2 surface, proper binding of CO to Pd, and the Pd–O–Sn interfaces were critical factors for the electrocatalytic selectivity and stability.